Model Post Disaster Reconstruction in Third World Countries, (Case of El Nino Emergency Project– Kenya) - Makhanu, K.S; Waswa, George; Masinde, G. W. (My University, 2007)
Following El Nino phenomena that occurred between November 1997 and March 1998, heavy rainfall all over the country caused floods that impacted thirty-five of the seventy-six administrative districts and the provincial city of Nairobi – Kenya. Many parts of the country were isolated due to transport system failure, and many essential services such as water supplies and health facilities were destroyed. There was loss of human lives and thousands of households were displaced. After the floods, there was an immediate need for emergency reconstruction works for vital infrastructure such as health services, water supplies, roads and bridges. The recovery funds were given by the World Bank, African Development Bank and Agense Franscaise de Developpement. A reconstruction management team was set-up in the Office of the President comprising private sector professionals under the special program, Project Management Unit (PMU). The management unit recorded a considerable reduction of implementation time and cost compared to normal project implementation procedures. This management system proved easily adoptable in any disaster situation for provision of immediate needs as well as the long-term reconstruction programs. This paper explores the operational systems that were adopted by the project management unit in the implementation of El Nino Emergency Projects as a basis of post disaster reconstruction model in third world countries.
Keywords: Post Disaster; Reconstruction; El-Nino Phenomenon; Project Management Unit; Kenya